Recent Developments on the Total Synthesis of Nakadomarin A. Issue 18 (14th May 2018) - Jana, Samaresh; Mekonnen, Habtamu Gelaw
Abstract: (‐)‐Nakadomarin A is an alkaloid belongs to manzamine family having architecturally complex structure and exhibits promising biological activities. To accomplish this target molecule, few novel synthetic strategies have been developed by eminent synthetic chemists. This review will highlight the important and improved synthetic approaches for the total synthesis of natural as well as unnatural isomers of nakadomarin A. All synthetic strategies have been enlightened from the cluster of literatures to develop a more elegant strategy for the molecule in future. Abstract : (‐)‐Nakadomarin A is an alkaloid belongs to manzamine family, having architecturally complex structure and exhibits promising biological activities. To accomplish this target molecule, few novel synthetic strategies have been developed by eminent synthetic chemists. This review will highlight the important and improved synthetic approaches for the total synthesis of natural as well as unnatural isomers of nakadomarin A. All synthetic strategies have been enlightened from the cluster of literatures to develop a more elegant strategy for this molecule in future.